(untitled) (Asia Pacific Journal of Social and Behavioral Sciences, 2017)
Life in rural Cambodia is difficult and rural women face issues such as gender-based violence, limited educational opportunities, and pressure to work while maintaining domestic roles. The current exploratory study examines the attitudes of rural Cambodian women (n = 48), framed within in context of migration to Thailand, with particular focus on the areas of community ailments, migration, and educational opportunities. Descriptive statistics indicate the persistence of an unhealthy community, with participants acknowledging the problems of domestic violence, crime, drug use, alcohol use, and depression. The data suggest some improvement in Cambodia, though participants nonetheless recognized working in Thailand as a competing option to the rural village life. Education is viewed positively, with evidence suggesting that the perceived benefits of education do not outweigh the economic push factors. As incoming aid money increases, before data will be helpful in guiding conclusions and informing decision making. Conclusions reflect a nuanced perspective of female participants’ agency given their challenging situation, reflecting informed decision making with informal risk analysis.